A high-performance photopolymer film material doped with silver nanoparticles and its preparation and application
By doping silver nanoparticles in photopolymer materials, the problem of easy dehydration and strong hydrophilicity of the material in humid environments is solved, and the stability and refractive index modulation of the material are improved, which is suitable for the preparation of holographic recording materials.
Patent Information
- Application Number
- CN201910320137.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-04-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2039-04-19
AI Technical Summary
Existing photopolymer materials are prone to dehydration in humid environments, have strong hydrophilicity, can cause cancer in long-term contact, and have a large shrinkage rate before and after polymerization, and have a low refractive index modulation system, which affects the performance of optical devices.
A photopolymer film material of acrylate-based photopolymer film doped with silver nanoparticles is used to disperse silver nanoparticles into acrylate monomers, and a photochemical reaction is used to generate a polymer grating film to improve the stability and refractive index modulation of the material.
It improves the stability of the material, reduces the shrinkage rate, increases the refractive index modulation system and diffraction efficiency, and reduces optical loss. It is suitable for the preparation of holographic recording materials.
Smart Images

Figure SMS_1 
Figure HDA0002034378090000011 
Figure HDA0002034378090000012
Abstract
Description
Technical Field
[0001] The invention relates to a high-performance photopolymer film material doped with silver nanoparticles, a preparation method and application thereof, and belongs to the technical field of films. Background Art
[0002] The exploration of new materials has always been the foundation for the development of various disciplines, and it also directly reflects the country's comprehensive national strength such as manufacturing capabilities, scientific and technological strength, economic strength and international competitiveness. As an important part of optical materials science, the synthesis and research of polymer materials used in optical devices have developed rapidly in recent years, and their use in industrial products has become more extensive, such as photorefractive materials, 3D printing materials, optical waveguide materials, nonlinear optical materials, biomedical materials, etc. The performance of optical polymer materials directly determines the quality and market competitiveness of related industrial products. Therefore, accelerating the development of optical polymers and improving the performance of their photopolymer device products are of vital importance to my country's scientific and technological development, industrial innovation and economic construction. In the decades of development of photopolymer materials, it has attracted attention from all walks of life in the late 20th century and early 21st century because of its good superiority as a volume holographic storage material, and has developed rapidly. Researchers have continuously optimized the performance of photopolymer materials by using different polymerization methods, changing the type of monomers, and doping nanoparticles such as liquid crystals, which has attracted the attention of all walks of life. In recent years, photopolymer materials have not only achieved good results in volume holographic storage, but various optical devices based on photopolymer materials, such as distributed feedback lasers (DFB), fiber Bragg gratings (FBG) and other devices, have also achieved remarkable development in the fields of biosensing and fiber-optic communications, jointly promoting the continuous development of photopolymer materials.
[0003] Photopolymer is a polymerization reaction based on light induction. It is a reaction in which free radicals or anions / cations are generated by photochemical methods to initiate the polymerization of monomer molecules. Monomers can be directly excited by light to cause polymerization, or photoinitiators or photosensitizers can be activated by light to initiate monomer polymerization, the latter of which is also called photosensitive initiated polymerization. Laser holographic recording materials generally use initiators to initiate polymerization. Initiation of polymerization is that the initiator first absorbs light and transitions to an excited state. The initiator in the excited state generates active seeds (free radicals or ions), which then initiate monomer polymerization. The photopolymer system used as a holographic recording material generally includes a photoinitiator, one or more monomers, a film-forming agent, etc. General photopolymer monomers are not sensitive to light and cannot directly produce polymerization, so photopolymerization initiators that are sensitive to a certain wavelength band are usually added to them.
[0004] The process of making holographic gratings with photopolymers is as follows: two coherent beams of light are projected at a certain angle onto the polymer monomer and nanoparticle substrate. Figure 1As shown in the figure, before exposure, the monomers and nanoparticles in the material are evenly distributed. During exposure, the two beams of light interfere on the surface of the material to form light and dark fringes. In this interference fringes mode, the monomer undergoes polymerization in the bright field. Due to the change in concentration gradient, the monomer molecules in the dark field diffuse to the bright field. At the same time, during the photopolymerization reaction, there is a chemical potential effect between the monomer and the nanoparticles, and mutual diffusion occurs between the two, driving the nanoparticles to diffuse from the bright field to the dark field. Due to the difference in density between the monomer and the polymer, the polymerization reaction will cause the volume of the material to shrink. Through diffusion, the nanoparticles effectively reduce the volume shrinkage caused by the photochemical reaction.
[0005] Common laboratory recording systems such as Figure 2 As shown in the figure, after beam expansion and collimation, the recording light (532nm) passes through a beam splitter and is split into two beams of light with the same polarization state and similar light intensity. After the light path direction is adjusted by a reflector, the two beams interfere at the sample placement location. The sample is placed in the interference field to undergo a photochemical polymerization reaction, and as the reaction proceeds, a volume grating with a periodic change in refractive index is formed in the sample. The detection light (633nm) is irradiated onto the sample, and the optical detector placed behind the sample monitors the sample polymerization reaction process in real time. The two probes (detectors) detect the transmitted light and the diffracted light respectively.
[0006] The photopolymer used to prepare optical devices must have high photosensitivity (>500cm / J), fast response speed, low shrinkage (<0.5%), large dynamic range, and the ability to quickly complete holographic recording; the recorded photopolymer grating has a high refractive index modulation degree (refractive index modulation degree>5×10 -3 ), high diffraction efficiency, good fidelity, non-volatile and other characteristics. The application of photopolymers to the preparation of optical devices (such as DFB, FBG) is usually based on photopolymer gratings. Therefore, the shrinkage rate of the material before and after polymerization and the refractive index modulation of the grating are the most concerned parameters in the preparation of optical devices.
[0007] In the process of photopolymer development, acrylamide (AA) and polyvinyl alcohol (PVA) were the first to form photopolymers using these two monomers. Photopolymer materials based on AA / PVA have the advantages of simple preparation method, low price and easy use. However, due to the high reactivity of AA / PVA photopolymers and good polymerization properties, this type of photopolymer material is highly hydrophilic, easily deliquesced in a humid environment, and long-term contact can cause cancer. The above problems are difficult to ignore when preparing optical devices.
[0008] In recent years, with the deepening of research on photopolymers, thiol and olefin monomers have entered the field of vision of scientific researchers. The small shrinkage rate of this material makes up for the shortcomings of the above materials to a certain extent. However, due to the small difference in the refractive index of thiol-olefin materials before and after polymerization, the refractive index modulation of this material has no obvious advantage in device preparation compared with other materials.
[0009] Compared with the above two photopolymer materials, polyacrylate photopolymers have the advantages of stable properties, a wide variety, wide applications, and low prices. They are the most practical materials for preparing optical devices and have received the most attention from researchers. However, their large shrinkage before and after polymerization is a problem that cannot be ignored when applying them to more aspects.
[0010] 1. Lower refractive index modulation;
[0011] 2. Lower diffraction efficiency;
[0012] 3. Large shrinkage rate;
[0013] 4. The material is sensitive to oxygen and water, has poor stability and short storage time;
[0014] 5. The thickness is large and the optical loss is large.
[0015] Acrylate photopolymers have been attracting attention from all walks of life due to their high sensitivity, wide dynamic range and low raw material prices, and have made a lot of research progress. Compared with the above materials, the materials prepared from acrylate monomers have a larger refractive index difference before and after polymerization, which is conducive to optimizing the refractive index modulation of the material, reducing the thickness of the material, and thus reducing the optical loss of the material. Summary of the invention
[0016] The purpose of the present invention is to overcome the problems in the prior art and provide a high-performance photopolymer film material doped with silver nanoparticles and its preparation and application.
[0017] A high-performance photopolymer film material doped with silver nanoparticles, characterized in that the raw material composition includes the following as shown in Table 1:
[0018] Table 1: Material composition and its function
[0019]
[0020] The acrylate monomer is selected from trimethylolpropane trimethacrylate (TMPTMA), trimethylolpropane triacrylate (TMPTA), pentaerythritol triacrylate (PETA), triethylene glycol dimethacrylate (TEGDMA) and other monomers, preferably trimethylolpropane trimethacrylate (TMPTMA). The photoinitiator is selected from N-phenylglycine (NPG), the photosensitizer is selected from Rose Bengal, and the nanomaterial dopant is selected from silver nanoparticles (Ag Nanoparticles), and gold nanoparticles (Au Nanoparticles) and gold nanorods (Au Nanorods) can also be selected, preferably silver nanoparticles.
[0021] The preparation of the polymer film material comprises the following steps: first, mixing acrylate monomer, photoinitiator and photosensitizer according to the mass ratio, heating and stirring until they are uniform; dispersing silver nanoparticles in an organic solvent; then, adding the silver nanoparticle dispersion to the mixed liquid material of the acrylate monomer obtained above, stirring evenly, placing in a closed container, vacuuming under light-proof conditions to volatilize the organic solvent, coating, and exposing at a wavelength of 532nm and an exposure intensity of 30mw / cm 2 ~100mw / cm 2 (Usually choose 50 mw / cm 2 ) under the catalysis of coherent light (generally fringe interference light) to produce a polymer grating film, which is not easy to deliquesce, has good stability, and the refractive index modulation degree is as high as nearly 0.007.
[0022] The high-performance photopolymer film material doped with silver nanoparticles obtained by the invention can be used as a holographic recording material.
[0023] In the process of researching new recording materials, in order to overcome the disadvantage of volume shrinkage due to polymerization and improve the refractive index modulation of the material, nanoparticle-doped photopolymer materials have attracted great attention in the field of holography. In the present invention, silver-doped nanoparticles (particle size ≤ 100nm) are selected as dopants of the material. The presence of silver and other nanoparticles affects the photochemical reaction process of the photopolymer material, effectively increases the refractive index modulation of the holographic grating prepared with the material, and reduces the volume shrinkage caused by the photochemical reaction. Material distribution is as follows: Figure 3 Commonly used acrylate monomers include methyl methacrylate, pentaerythritol triacrylate, dipentaerythritol pentaacrylate, etc. Most of the above monomers are suitable for the present invention.
[0024] The morphology of silver nanoparticles in the grating film and the grating morphology are as follows: Figure 4 As shown, Figure (a) is obtained by SEM test, and Figure (b) is measured by dark field microscopy.
[0025] Application as holographic recording material:
[0026] 1. Photonic Crystal Fiber
[0027] Photonic crystal fibers prepared using photopolymers can be used to develop fiber Bragg grating sensors, which have broad application prospects in biomedicine, environmental management, etc.; chirped gratings can be recorded on photonic crystal fibers to prepare wavelength division multiplexers, which has far-reaching significance for the development of fiber-optic communications. Uncured photopolymer solutions are injected into the fiber core, and coherent light is used to photocure and write gratings of different periods. The process is simple and can be replicated on a large scale. The materials in this patent have the advantages of simple preparation process, strong fluidity of the unpolymerized photopolymer solution, high grating refractive index modulation after photocuring, and high optical coupling efficiency, and are suitable for the preparation of photonic crystal fibers.
[0028] 2. Laser 3D anti-counterfeiting materials
[0029] Using the principle of double-beam interference, the object light and another coherent light (reference light) produce interference patterns, so that the photosensitive film can simultaneously record the phase and amplitude. This holographic recording method can record the three-dimensional information of the object, which can be reproduced in all directions. Different viewing angles produce different patterns. Therefore, encrypted information can be recorded at a specific angle, reproduced at that angle, and read, which can be applied to anti-counterfeiting technology. This patented material has stable properties, simple preparation, high diffraction efficiency, and clear reproduced images. It is an excellent material for recording anti-counterfeiting patterns.
[0030] Advantages of the present invention:
[0031] 1. By doping the material with Ag nanoparticles, the refractive index modulation of the material is increased;
[0032] 2. By doping the material with Ag nanoparticles, the diffraction efficiency of the material is increased;
[0033] 3. The doping of silver nanoparticles reduces the shrinkage of the material:
[0034] 4. Since the material is insensitive to oxygen and water, the stability and storage time of the material are enhanced;
[0035] 5. Reduce the thickness of the material from more than 100um to 10um, reducing the optical loss of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of the concentration diffusion of each component in the material before and after interference exposure;
[0037] Figure 2 Volume holographic storage optical recording system;
[0038] Figure 3 The distribution of materials in the holographic grating;
[0039] Figure 4 The morphology of Ag nanoparticles in the grating film (a) and the grating morphology (b);
[0040] Figure 5 Refractive index modulation curves at different silver nanoparticle doping concentrations (a) grating image reconstruction under white light irradiation (b);
[0041] Figure 6 Starting time diagram at different silver nanoparticle doping concentrations (a); dark field scattering diagram of silver nanoparticles dispersed in monomer solution (b), with the inset being its scattering spectrum; grating dark field scattering diagram without silver nanoparticle doping (c); grating dark field scattering diagram with 1wt% silver nanoparticle doping (d). DETAILED DESCRIPTION
[0042] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.
[0043] Example 1
[0044] Preparation steps of photopolymer grating materials
[0045] 1. Calculate the required mass of each component according to the mass ratio, and add a clean magnetic particle to the clean small brown bottle. Take a certain amount of TMPTMA and put it into the small brown bottle, and add 0.7wt% of photosensitizer Rose Bengal and 1.4wt% of initiator NPG. After adding a magnetic particle to the small brown bottle, place it in a heated magnetic stirrer and stir for 90 minutes, set the speed to 300r / min, and the heating temperature to 60℃. After 90 minutes, the photosensitizer Rose Bengal and initiator NPG are evenly dispersed in the TMPTMA solution. At this time, pay attention to avoid light.
[0046] 2. One-step method [1] The prepared silver nanoparticles (<120nm) were dispersed in xylene, ultrasonicated for 10min (120W, 40KHz), filtered and prepared into a 4mg / ml xylene solution. A certain mass ratio of the solution was added to the TMPTMA mixture. After the two solutions were stirred evenly, the small brown bottle was placed in a vacuum box with an open mouth and evacuated to a vacuum degree of 0.09MPa. A heating magnetic stirrer was placed in the vacuum box with a speed of 250r / min and a heating temperature of 60℃. Vacuum until the organic solvent is completely volatilized. This process should be protected from light.
[0047] [1] TYDong, WT Chen, CW Wang, CPChen, CN Chen, MCLin, JMSong, IG Chen, and THKao, "One-step synthesis of uniform silver nanoparticlescapped by saturated decanoate: Direct spray printing ink to form metallic silver films," Phys. Chem. Chem. Phys., 11, 6269-6275 (2009).
[0048] 3. Prepare a clean glass substrate, use a pipette to drop the prepared material on the glass surface, spread a flat thin strip film with a thickness of 20μm on both sides of the glass, then place another layer of glass on the material to control the thickness of the material and fix it with a binder clip.
[0049] 4. Use green light with a wavelength of 532nm to holographically expose the material to prepare a holographic grating.
[0050] The experimental data of holographic grating are as follows:
[0051] 1. High refractive index modulation and diffraction efficiency
[0052] The effect of silver nanoparticles doped in the material was explored, and a holographic interference optical path with a period of 1um was built. The exposure intensity of the material was 50mW / cm 2 The experimental results are as follows Figure 5 As shown in (a), the doping of silver nanoparticles will increase the refractive index modulation of the material. When the doping concentration reaches 1wt%, the refractive index modulation is the highest, reaching 0.0069. Figure 5 (b) shows the color reproduction image produced by reproducing the grating using white light, which can be used as an excellent holographic recording material.
[0053] Next, we continued to explore the effect of doping silver nanoparticles on the photopolymer holographic grating. Silver nanoparticles react with oxygen during the photochemical reaction of the photopolymer material, consuming oxygen and thus affecting the inhibition reaction between oxygen and free radicals. The start time of the photochemical reaction was shortened at different silver nanoparticle doping concentrations, and the start time was the shortest when the doping concentration was 1wt%, such as Figure 6(a) shows that the time for the inhibition reaction to occur is shortened. This experimental phenomenon can verify the above theory. In addition, silver nanoparticles produce plasmon effects in the local field through scattering. The scattering of silver particles and their scattering spectrum can be measured by dark field microscopy. The presence of silver nanoparticles increases the light intensity around them locally, strengthens the photochemical reaction, and affects the polymerization rate of the reaction. The dark field scattering image is shown in Figure 6 (b) As shown. By observing the grating sample under a dark field microscope, we can see the grating doped with silver particles. The silver particles are also distributed periodically, which can reduce the shrinkage of the material and increase the refractive index modulation of the material to a certain extent. Figure 6 (c)(d).
Claims
1. A high-performance photopolymer film material doped with silver nanoparticles, characterized in that: The raw material composition includes the following: The acrylate monomer is selected from trimethylolpropane trimethacrylate (TMPTMA), trimethylolpropane triacrylate (TMPTA), pentaerythritol triacrylate (PETA), triethylene glycol dimethacrylate (TEGDMA); the photoinitiator is selected from N-phenylglycine (NPG), the photosensitizer is selected from Rose Bengal, and the nanomaterial dopant is selected from silver nanoparticles (Ag Nanoparticles); Silver nanoparticle size ≤100nm; The thin film material preparation method comprises the following steps: firstly, acrylate monomer, photoinitiator and photosensitizer are mixed and heated and stirred according to the mass ratio until they are uniform; silver nanoparticles are dispersed in xylene, and then, the silver nanoparticle dispersion is added to the mixed liquid material of the acrylate monomer obtained above, and the mixture is stirred uniformly, placed in a closed container and vacuumed under light-proof conditions to volatilize the organic solvent, and a film is coated. At a wavelength of 532 nm, the exposure intensity can be 30 mw / cm 2 ~100 mw / cm 2 A photochemical reaction occurs under coherent photocatalysis to form a polymer grating film.
2. A high-performance photopolymer film material doped with silver nanoparticles according to claim 1, characterized in that: 14 parts by mass of photoinitiator.
3. A high-performance photopolymer film material doped with silver nanoparticles according to claim 1, characterized in that: Photosensitizer 7 parts by mass 4. The use of the high-performance photopolymer film material doped with silver nanoparticles according to any one of claims 1 to 3, characterized in that: The high-performance photopolymer film material is used as a holographic recording material.